Study of N2/He DC glow discharge. (March 2015) - Villa, M; Flores, O; Castillo, F; Reyes, P G; Martinez, H
Abstract: Optical emission spectroscopy and mass spectrometry measurement were used to study a gas mixture glow discharge of He and N2 at total pressure of 2.0 Torr, a power of 10 W and a flow of 16.5 l/min. The emission bands were measured in the wavelength range of 200 to 1100 nm. The principal species observed were N2 + (B 2 Σ + u →X 2 Σ + g ), N2 (C 3 Πu →B 3 Πg ), and He, which agree with mass spectrometry measurement.